Students' Expectations and Perceptions Regarding the Policies of Sexual Violence in Islamic Boarding Schools - Farida, Norma Azmi (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
This research explores the effectiveness of the policy on addressing sexual violence in Islamic boarding schools through the Gender Analysis Pathway. The study employs a qualitative approach using methods such as interviews, literature analysis, and document reviews. Interviews were conducted with female students of the Women Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUP-MI) Master and Doctoral Degrees from who have a background as alumni of Islamic boarding schools. Additionally, they have a focus on the study of women and children. The main document analyzed is the Ministry of Religious Affairs Regulation (PMA) Number 73 of 2022 concerning the handling and prevention of sexual violence in educational units under the Ministry of Religious Affairs. As this PMA does not yet have Standard Operating Procedures (SOP), it remains open to suggestions for effective implementation, which this research aims to accommodate. The research findings reflect the collective view of PKU-MI female students, who desire the PMA to be enforced with firmness and strict supervision. Furthermore, a bottom-up approach that takes into account the experiences of sexual violence victims is needed to activate feminist perspectives and promote the enforcement of gender-responsive policies.